Sikap Petani terhadap Pengolahan Lahan Tanpa Bakar Sebagai Salah Satu Upaya Pencegahan Kebakaran Lahan Gambut (Kasus di Kabupaten Mempawah Provinsi Kalimantan Barat) - Siti Sawerah; Ary Bakhtiar; Pudji Muljono; Prabowo Tjitropranoto (Universitas Muhammadiyah Malang, 2019)
West Kalimantan is one of province who often fire occurs in eac dry season. Various efforts have been conducted by the government in order to prevent fires. That efforts will be successful if have support of local farmers. One of their support can be analysis of attitude of farmers to land cultivation without burning system. The objectives of this study were: 1) to find out the attitude of farmers in land cultivation without burning system, 2) to analyze the correlation between the internal factors and the external factors to farmer’s attitude. This research was conducted in March to May 2015 in Mempawah District. The population were 95 95 farmers whose have land has ever been burned and land surround the burned area. The data collection was conducted by census on the population. Descriptive and correlational analysis was used to analyzed. The results indicated that the attitude of farmers to land cultivation without burning system was negative. The external factors were positively correlated with participation, consists of the extension worker’s role and support of social environment (public figures, the role of group, information media and government role). The internal factors correlated with attitude were education and income, the external factors were positively correlated with attitude.